Cerium incorporated MCM-48 (Ce-MCM-48) as a catalyst to inhibit bromate formation during ozonation of bromide-containing water: Efficacy and mechanism. (1st December 2015) - Li, Weiwei; Lu, Xiaowei; Xu, Ke; Qu, Jiuhui; Qiang, Zhimin
Abstract: The composite mesoporous sieve Ce-MCM-48 (cerium incorporated MCM-48) with different Si/Ce molar ratios were synthesized hydrothermally and characterized with X-ray diffraction, X-ray photoelectron spectroscopy, BET surface area, and pHpzc . Results indicate that Ce-MCM-48, especially with a Si/Ce molar ratio of 66 (i.e., Ce66 -MCM-48), could significantly inhibit bromate (BrO3 − ) formation during ozonation of Br − -containing water, achieving 91% of inhibition efficiency at pH 7.6 and 25 °C. An acidic or alkaline pH decreased the inhibition efficiency of Ce66 -MCM-48 to some extent, but reaction temperature ranging from 15 to 30 °C had no significant impact. By comparing the bromine mass balance, aqueous O3 decomposition, and newly formed H2 O2 between O3 and O3 /Ce66 -MCM-48 processes, the inhibition mechanism was proposed: Ce66 -MCM-48 promoted aqueous O3 decomposition to generate hydroxyl radicals (OH) that could merge into H2 O2, so the oxidative transformation of Br − and HOBr/OBr − by O3 and OH was primarily suppressed. The catalytic ability of Ce66 -MCM-48 was continuously regenerated through the circulating reactions between Ce(III) and Ce(IV) occurring on the catalyst surface. Besides its inhibition on BrO3 − formation, Ce66 -MCM-48 could also enhance the degradation of refractory organic micropollutants. Because of these distinct merits, Ce66 -MCM-48 has potential applications to water treatment by ozone. Graphical abstract: Highlights: Ce-MCM-48 inhibited BrO3 − formation during ozonation of Br − -containing water. The optimal molar ratio of Si/Ce was determined to be 66 for Ce-MCM-48. Ce66 -MCM-48 was well adaptive to typical pHs and temperatures for water treatment. Ce66 -MCM-48 promoted O3 decay and inhibited the oxidation of Br − and HOBr/OBr − . Ozonation of refractory organic micropollutants was enhanced by Ce66 -MCM-48.